Improving the accuracy of thermal power determination of VVER - V. I. Borysenko; D. V. Budyk; V. V. Goranchuk (Ядерна фізика та енергетика)
In most algorithms for forming control signals, locks and protection of VVER, the value of the reactor’s thermal power (RTP) is used. This article is dedicated to the analysis of the problem of determining the RTP of VVER-1000. The article suggests ways to improve the accuracy of the determination of RTP based on the signals of the neutron flux parameters control system at VVER-1000. The thermal power of the reactor is one of the important safety parameters of VVER-1000, and also this parameter determines the technical and economic parameters of the power unit. The task of increasing the accuracy of RTP determination is especially relevant considering plans to increase RTP of VVER-1000: in the first stage to 101.5 % of the nominal value, and later to 104 - 107 % of the nominal value, which equals to 3000 MW according to the project. In the article, the main factors influencing the errors of determination of RTP in different ways are considered: according to the thermal parameters of the 1st and 2nd contours and the parameters of the neutron flux in the Neutron Flux Monitoring System (NFMS) and In-core Monitoring System (ICMS). In order to improve the accuracy of determination of RTP in the NFMS, we propose a model that considers the influence on the signal of the ionization chamber of the following parameters: temperature and concentration of boric acid in the coolant, the position of the control rods, burning of fuel, etc. The results of the analysis of the change in RTP during the fuel campaign of VVER-1000 are given, which is determined in different ways.